Reflective writing in improving trainee teachers teaching skills in 21st century - Ariffin, Natasha; Zahruddin, Abdul Hafez (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
Fostering the best quality of trainee teachers during teacher education programme is essential to ensure that good quality teachers can be produced. One of the skills that should be cultivated among trainee teachers is the capability to adapt to new challenges especially in dealing with students of different races, backgrounds, characters, and religious beliefs since it is a routine in a teachers’ life. The capability to do so can be cultivated through reflective writing. This conceptual paper attempts to promote the role of reflective writing in teacher education programs in pursuing improvement and development of teaching skills. The emergence of information and communication technologies in this 21st century encourage the educators to rethink how and what reflective writing can be elevated in terms of its flexibility and interactivity. To give a clear overview of this raising matter, the idea of reflective writing and the importance of reflective writing will be discussed. Other than that, the authors will discuss further on what should be considered when involving in reflective writing and how to do reflective writing based on Kolb’s (1984) Experiential Learning theory.